2021
DOI: 10.3390/pr9122216
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Vehicle Exhaust Particle Number Regulations

Abstract: Vehicle emissions are a significant source of air pollution in cities. Particulate matter (PM) is a pollutant with adverse health effects. Regulations worldwide determine the PM exhaust emissions of vehicles by gravimetric quantification of the mass deposited on a filter over a test cycle. The introduction of particulate filters as vehicle exhaust gas aftertreatment devices led to low PM emissions. A particle number methodology (counting solid particles >23 nm), complementary to the PM mass measurement, was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(18 citation statements)
references
References 74 publications
0
18
0
Order By: Relevance
“…They concluded that control policies for condensable particles and their precursors are needed to further reduce the vehicle-exhaust-derived PNs in the environment. The 23 nm lower size does not always cover the whole or the largest part of the size distribution of the emitted particles, as highlighted in a recent review [ 274 ] and references therein. High amounts of sub-23 nm particles are measured very often, both for diesel and gasoline direct-injection vehicles, but in particular for the technologies not subject currently to a SPN limit (port fuel injection gasoline and gas engines).…”
Section: Mitigation Measures For Road Traffic Pm Emissions and Its Im...mentioning
confidence: 99%
“…They concluded that control policies for condensable particles and their precursors are needed to further reduce the vehicle-exhaust-derived PNs in the environment. The 23 nm lower size does not always cover the whole or the largest part of the size distribution of the emitted particles, as highlighted in a recent review [ 274 ] and references therein. High amounts of sub-23 nm particles are measured very often, both for diesel and gasoline direct-injection vehicles, but in particular for the technologies not subject currently to a SPN limit (port fuel injection gasoline and gas engines).…”
Section: Mitigation Measures For Road Traffic Pm Emissions and Its Im...mentioning
confidence: 99%
“…However, with the increasing awareness of the harm of particulate emissions from vehicles [14,15], governments and environmental agencies have imposed more stringent regulations and standards for vehicle emissions, along with higher testing requirements, making particulate matter detection increasingly important. There has been a significant shift in recent years from traditional particle mass (PM) measurements to particle number (PN) measurements for particulate detection [16][17][18], with a particular focus on the quantity and size distribution of fine particles [18,19]. Therefore, the independent development of equipment suitable for measuring particulate number concentration in in-use vehicles in China is of great significance.…”
Section: Introductionmentioning
confidence: 99%
“…The PN method was introduced in the EU regulation for light-duty diesel vehicles in 2011. The PM and PN limits were extended to gasoline vehicles with direct injection engines, heavy-duty engines, and non-road mobile machinery (NRMM) [2,3]. A similar method has also been proposed for measurement of particles from brake emissions [4].…”
Section: Introductionmentioning
confidence: 99%
“…CPCs are instruments that optically count particles using light scattering after their growth to micron size in a supersaturated environment [9,10]. The CPCs of the laboratory systems have strict linearity requirements (±5%), while the PEMS more relaxed (±15%) [2].…”
Section: Introductionmentioning
confidence: 99%